MANAGEMENT OF DA'WAH OF THE SOUTHEAST ACEH ISLAMIC SHARIA OFFICE IN STRENGTHENING THE FAITH OF MUSLIMS IN BORDER AREAS - Asmar, Dailami; Soiman (Department of Research and Community Service at the Ummul Quro Al-Islami Bogor Institute, 2025)
Faith is a firm and definite belief or faith, without the slightest doubt, which includes faith in Allah, angels, books, apostles, the Day of Judgment, and qada and qada. This study aims to analyze the management of the Southeast Aceh Islamic Sharia Office in strengthening the faith of Muslims in the border area, Southeast Aceh Regency. The research method used in this study is qualitative which describes and analyzes findings in the field, The type of data used is primary data from interview results and secondary data is in the form of previous books or journals related to the title of this research. The data collection techniques used in this study are interviews, observations and documentation. The results of this study show that the da'wah management of the Southeast Aceh Islamic Sharia Office has carried out planning, organizing, movement and supervision in strengthening the faith. The da'wah programs carried out include routine recitation, da'i placement in border areas, da'wah safaris, wirid yasin, commemoration of Islamic holidays, appeals to wear Islamic clothing and training da'i and da'iyah cadres. In addition, the Islamic Sharia Office also fosters ustadz and border da'i to provide Islamic religious education to the local community so that their faith is maintained